Measurement of <mtext>D</mtext>s−<mtext> → τ</mtext>−<mtext>ν</mtext>τ and a new limit for <mtext>B</mtext>−<mtext> → τ</mtext>−<mtext>ν</mtext>τ. - Dova, María Teresa (1997)
Using a data sample of 1 475 000 Z → qq̄(γ) events collected during 1994 with the L3 detector at LEP, we have studied the purely leptonic decays of heavy flavour mesons, <mtext>D</mtext>s−<mtext> → τ</mtext>−<mtext>ν</mtext>τ and <mtext>B</mtext>−<mtext> → τ</mtext>−<mtext>ν</mtext>τ. A signal is observed in the invariant mass distribution M(γDs−) corresponding to the decay sequence <mtext>D</mtext>∗−<mtext> → γD</mtext>s−, <mtext>D</mtext>s−<mtext> → τ</mtext>−<mtext>ν</mtext>τ, <mtext>τ</mtext>−<mtext> → l</mtext>−<mtext>ν</mtext>l<mtext>ν</mtext>τ. The branching fraction for <mtext>D</mtext>s−<mtext> → τ</mtext>−<mtext>ν</mtext>τ decays is measured to be <mtext>β</mtext><mtext>(D</mtext>s−<mtext> → τ</mtext>−<mtext>ν</mtext>τ<mtext>) = 0.074 ± 0.028(stat) ± 0.016(syst) ± 0.018(norm)</mtext>. No signal of <mtext>B</mtext>−<mtext> → τ</mtext>−<mtext>ν</mtext>τ decays is observed in the data, corresponding to an upper limit on the branching franction <mtext>β(</mtext><mtext>B</mtext>−<mtext> → τ</mtext>−<mtext>ν</mtext>τ<mtext>) < 5.7 × 10</mtext>−4 at 90% CL.